Applications and market of PVC for piping industry - Martins,Johnny De N. (2009)
The use of plastic materials by the piping industry accounts for a significant volume of polymers. In this segment PVC represents the largest worldwide market for plastics. PVC is often used in plastic pressure pipe systems for pipelines in the water and sewer industries because of its inexpensive nature and flexibility. Pipes and fittings constitute the largest volume application at 40% of the marketplace. This paper discusses the piping extrusion process and the worldwide PVC market, emphasizing the Brazilian market. It is also presented a case study including an overall cost calculation for making an extrusion line for PVC piping.